Psychological processing among caregivers of allogeneic bone marrow transplant recipients: Qualitative findings from a longitudinal study. Issue 3 (4th May 2023) - Tan, Kelly; Fredrickson, Barbara; Santos, Hudson; Wood, William; Schwartz, Todd; Mayer, Deborah
Abstract: Purpose: To describe caregiver psychological processing during the 12 weeks after transplant and the potential role of positive emotions in caregiving experiences. Methods: We conducted a longitudinal qualitative descriptive study and interviewed 11 BMT caregivers monthly for 12-weeks post-transplant about their experiences and psychological processing. We analyzed 38 interviews using directed content analysis based on guiding theories and inductive in vivo coding to develop themes. Results: The majority of participants appraised caregiving as a challenge that needed to be met. Caregivers described feeling positive emotions throughout the time after transplant (gratitude, interest, and hope). We identified two new themes: mirroring (caregiver feelings reflecting patient status) and emotion regulation (hiding negative emotions and displaying positive emotions when with the patient). Implications: Findings provide further evidence that interventions focused on emotion regulation and positive emotion experiences during caregiving to reduce the negative effects of caregiving related stress may be promising.